HEDONISTIC AND UTILITARIAN MOTIVATIONS TO VISIT A MALL (INTERNATIONAL SEMINAR, 2024)
This study aims to analyze the motivation experienced by consumers to visit Queen City Mall, namely whether it includes hedonistic or utilitarian motivation. Hedonistic and utilitarian motivations are interrelated in driving consumer behavior, where hedonic motivation provides for fear of missing out and impulse buying focuses on fulfilling emotional pleasure and immediate experience, in contrast, utilitarian motivation provides for efficiency and achievement, is oriented toward meeting functional needs and practical goals. This study uses a questionnaire as a means of collecting respondent data. Data analysis was carried out using descriptive analysis methods to provide an overview of shopping behavior and motivation experienced by consumers. The focus of this research is all visitors to Queen City Mall. The sample in this study was taken using purposive sampling, with a total sample of 59 people. The results showed that consumers at Queen City Mall have a higher level of utilitarian motivation compared to hedonic motivation. In addition, efficiency has a much larger number of respondents who choose achievement.  The mall manager needs to develop marketing that suits consumer needs so that it can increase the number of visitors and higher revenue.